MODEL-BASED ACCOUNTING RESEARCH STUDY OF CONSEPT MAP - Yuli Chomsatu; Indra Maulana (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2019)
The research aims to implement the Consept MAP model in accounting research. The model is expected to improve the student's ability in conducting accounting research stages. This study was conducted on students of the Uniba Surakarta Accounting study Program of 6 years of doctrine 2018/2019 taking accounting research courses. The Consept Map Learning Model (concept map) is a term about the strategy teachers use to help students organize the concepts of lessons that have been studied based on the meaning and relationship between their components (Novak, 1984 and G Awith, 1988). The relationship between one concept and the other concept is known as a proposition. The concept map is an effective tool presenting visually the generalization-generalization hierarchy and to express the interconnectedness of the proposition in the system of interconnected concepts. The results showed there was a difference in the student's value in conducting accounting research before and after implementing the Consept Map learning method. Using the concept map method, learning to improve students ' ability to perform research stages. Keywords: Learning Methods, Consept Map